The shattered lens : a war photographer's true story of captivity and survival in Syria - Alpeyrie, Jonathan; Luczkiw, Stash; Timmermann, Bonnie (Atria Books, 2017)
"Discover a gripping and harrowing tale of war and torture from the man who lived it in this powerful memoir by the celebrated war journalist who not only documented over a dozen conflict zones worldwide but was also captured and held hostage by Syrian rebels in 2013. Capturing history was Jonathan Alpeyrie's job but he never expected to become a news story himself. For a decade, the French American photojournalist had weaved in and out of over a dozen conflict zones. He photographed civilians being chased out of their homes, military trucks roving over bullet-torn battlefields, and too many bodies to count. But on April 29, 2013, during his third assignment to Syria, Alpeyrie was betrayed by his fixer and handed over to a band of Syrian rebels. For eighty-one days he was bound, blindfolded, and beaten. Not too far away, President Bashar al Assad's forces and those in opposition continued their bitter and bloody civil war. Over the course of his captivity, Alpeyrie kept his spirits up and strived to see, without his camera lenses, the humanity in his captors. He took part in their activities, taught them how to swim, prayed with them, and tried learning their language and culture. He also discovered a dormant faith within himself, one that strengthened him throughout the ordeal. Captured by History is the firsthand account of a photojournalist who has always answered the next adrenaline-pumping assignment. Yet, during his headline-making kidnapping, he was left to consider the value and risks of his career, ponder the violent conflicts he had seen, and put the historical events over which we have no control into perspective"--Provided by publisher.